Simplifique a expressão:
x∛(x^2 ) + 5.x^(5/3) - 6∛(x^5/3 )
Soluções para a tarefa
Respondido por
0
Bom dia
x∛(x^2 ) + 5.x^(5/3) - 6∛(x^5/3 )
= x*x^(2/3) + 5*x^(5/3) - 6*x^(5/9)
= x^(5/3) + 5*x^(5/3) - 6*x^(5/9)
= 6 * ( x^(5/3) - x^(5/9) )
x∛(x^2 ) + 5.x^(5/3) - 6∛(x^5/3 )
= x*x^(2/3) + 5*x^(5/3) - 6*x^(5/9)
= x^(5/3) + 5*x^(5/3) - 6*x^(5/9)
= 6 * ( x^(5/3) - x^(5/9) )
Perguntas interessantes
Informática,
10 meses atrás
Física,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás